Facile synthesis of goethite anchored regenerated graphene oxide nanocomposite and its application in the removal of fluoride from drinking water. Issue 58 (13th December 2016) - Fan, Yunfang; Fu, Dandan; Zhou, Siqi; Lu, Yiqing; Zhao, Xiaoxi; Jin, Wei; Zhao, Yaping
Abstract: Drinking water fluoride pollution is a worldwide environmental problem imposing serious menace to human health. Goethite anchoring regenerated graphene oxide (α-FeOOH@rGO) nanocomposite was synthesized via facile one-step hydrolysis pathway with ferrous sulfate as starting material. Fluoride adsorption efficiencies in aqueous solution were also testified through batch adsorption experiments. α-FeOOH@rGO has good defluoridation ability in a wide range of pH and has a strong anti-interference ability in the presence of high concentration foreign anions. Pseudo-second-order adsorption kinetics and Langmuir adsorption isotherms are fitted well involved in fluoride adsorption process. The FTIR and XPS results prove that defluoridation proceeds through an ion-exchange mechanism with sulfate-bearing in α-FeOOH@rGO crystal structure. It would be useful for the purpose of environmental protection in design and improvement of α-FeOOH@rGO as a cost-effective anion-exchange adsorbent.